Central Council and issue of local self-government reform: november 1917 – april 1918 (on the occasion of centenary of Central Council establishment) - Kozachenko, Anatolij Ivanovich (Theory and practice of jurisprudence, 2017)
The article deals with the activities of the Central Council which intended to carry out a local self-government reform. The Third Universal of the Central Council provided for expansion of powers of zemstvo self-government but subordinated them to the General Secretariat of the Internal Affairs, which is contrary to democratic principles of local self-government. Expansion of zemstvo powers was provided by the “Law on Elections to the Constituent Assembly of the UPR” (Ukrainian People’s Republic) on 16 November 1917, according to which organization and conduct of elections were relied on local self-government. Aggression of the Bolshevik Russia and deepening the crisis of zemstvo self-government forced the Central Council to declare extraordinary elections to people’s (zemstvo) councils and introduction of a brand new system of local self-government by the Fourth Universal of 9 (22) January 1918. On March 6, 1918, the Central Council adopted the Law “On Administrative and Territorial Division of Ukraine” which provided “establishment of new bodies of self-government and authorities” due to liquidation of provinces and districts and establishing a division of the UPR into states. However, the Central Council failed to implement this law and zemstvos continued to perform the functions of local self-government. The policy of the Central Council, which had the goal to eliminate zemstvo self-government, caused deterioration of relations between zemstvos and the Central Council. To preserve zemstvo self-government, representatives from seven provincial boards established the All-Ukrainian Union of Zemstvos in April 1918. But establishment of theUniondid not contribute to overcoming the economic and fiscal zemstvo crisis and led to deepening the process of politicization of zemstvo self-government. The Constitution of the UPR of 1918 provided a three-tier system of local self-government in which the leading role was given to a local element – a community. The Constitution of the UPR was based on the key democratic principles of local self-government arrangement, provided for mechanisms of power decentralization. However, it is known that the Constitution of the UPR of 1918 could not be enforced due to a loss of the state power by the Central Council. The reform of local self-government in the UPR was hindered by aggression of the Bolshevik Russia, conditions of internal political instability and social and economic crisis. However, these were inadvertences made by the Central Council that were the main reason for failure of the reform.